Causality of Consumption, Government Expenditure, and Distribution of ZIS Funds (Zakat Infaq and Shodaqoh) on Indonesia's Economic Growth - Permadi, Andrean; Eni Susilowati; Sri Hariyanti; Dewi Nur Alfa Damayanti (HM Publisher, 2022)
From the Islamic economic perspective, there are factors that can influence economic growth, namely the distribution of ZIS funds. The distribution of ZIS funds can be used to encourage economic growth in a positive direction. This study aimed to examine how the direction of the relationship between consumption, government expenditure, and distribution of ZIS funds has on Indonesia's economic growth. The method used is a quantitative approach, using Granger causality data analysis techniques and cointegration tests. The data used is secondary data from the Central Bureau of Statistics with the type of time series data. This study shows that there is a two-way causality between household consumption and Indonesia's economic growth. There is a one-way causality between government expenditure and Indonesia's economic growth, where Economic growth affects government expenditure and not vice versa. There is a one-way causality between the distribution of ZIS funds to Indonesia's economic growth, where the distribution of ZIS funds affects economic growth and not vice versa.